Reactivity of posterior cortical electroencephalographic alpha rhythms during eyes opening in cognitively intact older adults and patients with dementia due to Alzheimer's and Lewy body diseases - Babiloni, Claudio; Lorenzo, Ivan; Lizio, Roberta; Lopez, Susanna; Tucci, Federico; Ferri, Raffaele; Soricelli, Andrea; Nobili, Flavio; Arnaldi, Dario; Famà, Francesco; Buttinelli, Carla; Giubilei, Franco; et al. (Elsevier Inc., 2022)
Please modify the Abstract as follows:Here we tested if the reactivity of posterior resting-state electroencephalographic (rsEEG) alpha rhythms from the eye-closed to the eyes-open condition may differ in patients with dementia due to Lewy Bodies (DLB) and Alzheimer's disease (ADD) as a functional probe of the dominant neural synchronization mechanisms regulating the vigilance in posterior visual systems.We used clinical, demographical, and rsEEG datasets in 28 older adults (Healthy), 42 DLB, and 48 ADD participants. The eLORETA freeware was used to estimate cortical rsEEG sources.Results showed a substantial (> -10%) reduction in the posterior alpha activities during the eyes-open condition in 24 Healthy, 26 ADD, and 22 DLB subjects. There were lower reductions in the posterior alpha activities in the ADD and DLB groups than in the Healthy group. That reduction in the occipital region was lower in the DLB than in the ADD group.These results suggest that DLB patients may suffer from a greater alteration in the neural synchronization mechanisms regulating vigilance in occipital cortical systems compared to ADD patients.
Keywords: Alzheimer's Disease (AD); Dementia With Lewy Bodies (DLB); Desynchronization of Alpha Rhythms; Exact Low-Resolution Brain Electromagnetic Source Tomography (eLORETA); Eyes Closed; Eyes Open; Resting State Electroencephalographic (EEG) Rhythms